The Effect Of Experiential Marketing And Perception Of Product Quality Through Costumers Satisfaction: Study at Costumers of Toyota Auto2000 Showroom In Bandar Lampung City - Utomo, Rafi Abhisoko (Jurnal Kompetitif Bisnis, 2021)
This research aimed to find out the effect of experiential marketing, perception of product quality through customer satisfaction to customer of Toyota Auto2000 showroom in Bandar Lampung City. This research applies the explanatory type with quantitative approach. The population in this study were customers of Toyota Auto2000 showroom in Bandar Lampung City. The sampling technique in this research used nonprobability sampling with accidential sampling technique with sample of 100 respondents. The data were obtained from questionnaire through likert scale. The data analysis used was descriptive analysis, and multiple linear regression analysis. Testing the hypothesis using the t test, F test and R2 test. Based on the results of the research and data analysis, experiential marketing has a positive and significant effect on the variable of customer satisfaction level, perception of product quality has a positive and significant effect on the variable of customer satisfaction level. Experiential marketing and perceived product quality have a positive and significant effect together on consumer satisfaction.